Adaptive Strategic Planning in Islamic Educational Institutions in Responding to Internal and External Environmental Change - Agustina, Muvtia; Putri, Octa Romadhona; Rahmatullisa, Siti; Sirozi, Muhammad (Yayasan Sembilan Pemuda Indonesia, 2026)
The growing complexity of educational environments in the 21st century driven by rapid technological advancements, globalization, and shifting societal expectations has required educational institutions to adopt more adaptive and responsive strategic approaches. Within this evolving landscape, Islamic educational institutions encounter a distinctive challenge in balancing the demands of modernization with the preservation of religious values and institutional identity. Despite extensive discussions on strategic planning and digital transformation, limited research has systematically conceptualized adaptive strategic planning as an integrated framework specifically suited to Islamic educational contexts. This study aims to address this gap by developing a conceptual framework of adaptive strategic planning that incorporates both internal and external environmental dimensions. Using a qualitative conceptual literature review, this research synthesizes scholarly works published between 2020 and 2025, focusing on leadership, organizational culture, human resource capacity, and technological integration as key determinants of institutional adaptability. The findings suggest that institutional adaptability emerges from the dynamic interaction between internal capacities such as transformational leadership, a learning-oriented culture, and teacher digital competence and external pressures, including technological disruption, globalization, policy changes, and evolving societal expectations. Furthermore, adaptive strategic planning is characterized by flexibility, iterative decision making, continuous evaluation, and active stakeholder engagement, all of which contribute to strengthening institutional resilience. Importantly, this study highlights that adaptability in Islamic educational institutions must be grounded not only in managerial effectiveness but also in ethical and religious values, ensuring that innovation does not compromise institutional identity. This dual orientation offers a context-sensitive contribution to the literature. However, the study is limited by its conceptual nature and recommends future empirical validation through case studies or mixed-method approaches.